Cudskie drevnosti Rifeâ : permskij zverinyj stil' = The animal style of Perm - Oborin, Vladimir Antonovič; Cagin, Georgij Nikolaevič (Iskusstvo Prikam'â, 1988)
Summary.
Keywords: eläimet; kansantaide; korut; permiläiset kansat; suomalais-ugrilaiset kansat; djur; folkkonst; smycken; permiska folk; finsk-ugriska folk